2005
DOI: 10.17660/actahortic.2005.673.13
|View full text |Cite
|
Sign up to set email alerts
|

Propagation Studies on Chilean Geophytes

Abstract: Chilean geophytes are distributed throughout the country, between Arica (18°29' South latitude) and Tierra del Fuego (54°20' South latitude). However, the greatest diversity is concentrated in the central part of the country, which has a Mediterranean climate. There are about 40 genera, and, depending on the species, they have a great potential either as garden plants or as cut flowers. A 4-year study was conducted to test different methods of both sexual and vegetative propagation on 19 species:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 8 publications
(8 reference statements)
0
17
0
Order By: Relevance
“…Besides, the karyotype was also described, indicating that P. australis has an asymmetric karyotype with haploid form 2m + 4sm + 2st. On the other hand, Schiappacasse et al (2005) reported different types of sexual and asexual propagation in different geophytes plants from Chile, including P. australis. With respect to genetic variation, no studies have been informed in this species.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the karyotype was also described, indicating that P. australis has an asymmetric karyotype with haploid form 2m + 4sm + 2st. On the other hand, Schiappacasse et al (2005) reported different types of sexual and asexual propagation in different geophytes plants from Chile, including P. australis. With respect to genetic variation, no studies have been informed in this species.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that seed germination over 85% of L. coquimbensis and L. purpurea happens at 10°C (De la Cuadra et al, 2002;Jara et al, 2006); for L. coquimbensis, L. purpurea, and L. ixioides germination is near zero at 20°C (Schiappacasse et al, 2005); and in L. purpurea, seed germination is totally inhibited at 25°C (Jara et al, 2006). Although optimal germination temperature is unknown, the studies above indicate that temperatures at or above 20°C inhibit germination and at 10°C germination is enhanced.…”
mentioning
confidence: 98%
“…lahue, it would be feasible to increase the number of bulbils through methods of artifi cial vegetative multiplication such as bisection (Schiappacasse et al, 2003) or in vitro cultivation. Alternatively, propagation could be performed by seeds, which may reach high percentages of germination (89 to 100%) at 15 or 20ºC (Schiappacasse et al, 2003(Schiappacasse et al, , 2005.…”
Section: Discussionmentioning
confidence: 99%
“…lahue is a bulbous plant with ornamental potential because of its attractive foliage -similar to small palm leaves -and its delicate colorful fl owers, which have the appearance of small irises (Figure 2) (Hoffmann, 1989;Bridgen et al, 2002;Schiappacasse et al, 2003). The fl owering season, foliage permanence, vegetative propagation and seed propagation of "lahue" have been previously studied (Schiappacasse et al, 2003(Schiappacasse et al, , 2005. However, it is necessary to optimize crop management, and specifi cally, to know the effect of bulb weight on the fl owering and multiplicative capacity of this species.…”
Section: Introductionmentioning
confidence: 99%